The impact of volunteer tourism on local communities: A managerial perspective. (3rd May 2018) - Hernandez‐Maskivker, Gilda; Lapointe, Dominic; Aquino, Rayssa
Abstract: Volunteer tourism, as a potential tool for community development and sustainability, has been gaining the attention of researchers for the past decade. However, little empirical research exists about the impact of this activity on the host communities from the managerial point of view. The research, based on a qualitative study of managers' opinions from volunteer tourism organizations' leading programs worldwide, not only emphasizes the impacts of voluntourism but also suggests moving from a top‐down style of volunteering to a cocreation process. Contradictions emerge from the discourses of managers regarding the positive, negative, and long‐term impacts of voluntourism, and managerial implications are suggested.